KEBIJAKAN NASIONAL DALAM KONTEKS LOKAL: TANTANGAN IMPLEMENTASI KEBIJAKAN DESA SIAGA DAN RUJUKAN PELAYANAN KESEHATAN DI KABUPATEN KEPULAUAN YAPEN PAPUA - Supriyati, Yosef Leu Maing Deni Kurniadi Sunjaya (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background:One of the policies in health to achieve IndonesiaSehat 2010 was the development of desa siaga that wasbased on Decree of Ministry of Health number 564/MENKES/SK/VIII/2006 regarding the guidance on the implementation ofDesa Siaga. Desa Siaga is a community based health effortthat involved community self funding agency such as PKK,religious organization, and private sector.Method:This was a qualitative descriptive research that usedexplanatory analysis with case study design. The researchinformant was district government, health office, communityleaders and public figure as well as health care provider. Thedata was collected with interview, observation anddocumentation. Data analysis was conducted with case studyanalysis.Result: This research showed that the implementation of DesaSiaga was with topâdown method that used social mobilizationapproach. The district government and community was verymuch supporting the policy of Desa Siaga. Difficult geographiclocation, limited human resources in health and limited fundingwere the main obstacles in the implementation of Desa Siagapolicy and health service referral. The main problem of referralimplementation was transportation and funding. The readinessof community and village aparatur to assist the poor communitywas still very minimum.Conclusion: This research proven that Desa Siaga programwas very important for community in the district of Yapenarchipelago. Nevertheless, difficulties in geographiccondition,limited human resources in health as well as limited fundinghas resulted in difficulties in the implementation of Desa Siagapolicy and health service referral in the district of Yapenarchipelago. The regional and central government have notbeen able to respond to the needs of Desa Siaga.Keyword: Policy Implementation, Desa siaga, Papua.